If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9n + -20 + 4n = 7n + 16 Reorder the terms: -20 + 9n + 4n = 7n + 16 Combine like terms: 9n + 4n = 13n -20 + 13n = 7n + 16 Reorder the terms: -20 + 13n = 16 + 7n Solving -20 + 13n = 16 + 7n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7n' to each side of the equation. -20 + 13n + -7n = 16 + 7n + -7n Combine like terms: 13n + -7n = 6n -20 + 6n = 16 + 7n + -7n Combine like terms: 7n + -7n = 0 -20 + 6n = 16 + 0 -20 + 6n = 16 Add '20' to each side of the equation. -20 + 20 + 6n = 16 + 20 Combine like terms: -20 + 20 = 0 0 + 6n = 16 + 20 6n = 16 + 20 Combine like terms: 16 + 20 = 36 6n = 36 Divide each side by '6'. n = 6 Simplifying n = 6
| 60+7x=13x-8 | | 9-2y=y+2(4y-5) | | 4n-5(n+2)=7-3(3-n) | | 67+92x=92 | | 2/4+2/4+x=3 | | 4/3=5/8a+14/3 | | -5x-3(3x+10)=138 | | -3(2x-3)=4(5-x) | | 2(3z-1)=16 | | 3(x-8)=7 | | 3x+8x-14=30 | | 3(x-4)+37=2x | | 1.3y+7.8=1.3 | | 5x-6=5*5+3 | | -4w+4=0 | | 6x+2-3x+9=0 | | x/2+x/3*4=5 | | -2x-6(3x+10)=40 | | 14+2y=2(y+3) | | (5x-4)(3x+2)=0 | | 100+10=x+15 | | 7(x+4)+8=8(2x-6) | | 5r=16-(2r+8) | | 9-x+2=2x+3x | | 4x-4(x+4)=5(x+4) | | 2(3(-3)-2)+-3=9 | | (3x-5)(9x+7)=0 | | 2x-5(3x-8)=118 | | 7x+8-10x-12=9x-6x+8 | | 10(2x-4)+20=5(4x-3)+18+3x | | 6a+7-a=-17 | | -4(2x-3)=4x-18+3x |